Standardisasi Rumah Potong Unggas Berbasis Prinsip Halal, Thayyib dan Ihsan: Tinjauan Integratif Multi-Perspektif Sains dan Syariat - Hajah Thaha, Aminah; Ahmad, Arifuddin; Dirhamzah, Dirhamzah; Hafsan, Hafsan (Anoa: Journal of Animal Husbandry, 2026)
The acceleration of the commercial poultry industry demands a paradigm shift in quality assurance, moving from formal halal certification to a holistic fulfillment of halal, thayyib, and ihsan principles. Operational deviations in the field, such as introducing birds that are not completely dead into the scalding tank, represent a fatal critical control point that diminishes both sharia validity and carcass biological quality. This comprehensive review aims to synthesize prior scientific findings to construct a future Poultry Slaughterhouse standardization framework that integrates animal science, biology, and Islamic sharia perspectives. The methodology applied a systematic review approach of indexed scientific articles from Scopus, ScienceDirect, Sinta, and Garuda databases published between 2016 and 2026. The extracted data were tabulated into a synthesis matrix for critical analysis. The findings indicate that bleeding failure causes live chickens to drown in hot water, altering the carcass's legal status into carrion (maitah). Biologically, this phenomenon triggers extreme distress, causing a corticosterone spike that disrupts postmortem glycolysis, reduces water-holding capacity, and produces Pale, Soft, Exudative (PSE) meat characteristics highly susceptible to pathogenic bacterial contamination. Animal science engineering recommends calibrating conveyor speed to secure a minimum bleeding time of 90–120 seconds, or utilizing cone killers in non-industrial settings to mitigate pre-slaughter stress and ensure single-cut accuracy. Modern PSH standardization must unify administrative religious audits with empirical laboratory parameters by establishing new critical control points and appointing dual-competence quality control officers.